Optimization of PV array tilt angle for minimum levelized cost of energy. (December 2021) - Osmani, Khaled; Ramadan, Mohamad; Lemenand, Thierry; Castanier, Bruno; Haddad, Ahmad
Abstract: This paper studies the effects of PhotoVoltaic (PV) tilt angle variation over the cost efficiency of PV networks. The monthly modification of the tilt angle β conducted by this study, decreased the levelized cost of energy (LCOE), thus enhancing the system's economical status, by reducing its capital investment's payback period. The intended outcome of this work is twofold: it corresponds to a generalized novel mathematical model which enables the maximum number of PV panels to be fit into a square shaped area without any mutual shading, plus it investigates the monthly tilt angle values based on a specific selection, and their effects on the LCOE. The application of the obtained results (i.e., numerical values of β) has diminished both the LCOE as well as the power cost, while increasing power production for a PV system located in Tripoli-Lebanon (latitude: 34.38°), Belfort-France (latitude: 47.63°) and Tantan-Morocco (latitude: 28.38°).